PEMBUATAN YOGHURT MURBEI HITAM (MORUS NIGRA L.): PROPORSI SARI BUAH DAN SUSU SAPI TERHADAP KOMPONEN BIOAKTIF DAN VIABILITAS BAKTERI ASAM LAKTAT SELAMA PENYIMPANAN - Oeitanto, Andy; Nugerahani, Ira; Kusumawati, Netty (Widya Mandala Surabaya Catholic University, 2013)
Yoghurt is made from milk processing through fermentation by Lactic Acid Bacteria (LAB), Lactobacillus bulgaricus and Streptococcus thermophilus. Adding black mulberry’s juice can improve yoghurt’s functional characteristic through anthocyanin. Bioactive compounds was known unstable on storage and reportedly capable both to inhibit pathogen bacteria’s and stimulate LAB’s growth. The aim of this research is observe the effects of different proportion of fresh juice and cow’s milk, storage time and the interaction both of them on bioactive compounds and viability of LAB. This research used factorial Randomized Block Design (RBD) with two factors, proportion of fresh juice with fresh cow’s milk 5:95 (M1), 10:90 (M2), 15:85 (M3) % (v/v) and storage time 3 (L1), 10 (L2), 20 (L3) days with three replications. The parameters observed were total phenol, total flavonoid, anthocyanin content, total of LAB and pH as complement data. Data statistically analyzed by ANOVA test (Analysis of Variance) at α = 5% and continued with DMRT (Duncan's Multiple Range Test) at α = 5%. Used different proportion of fruit juice and storage time had significant effect on bioactive compounds and viability of LAB but there is no interaction both of them. The higher level proportion of fresh juice made amount of bioactive compounds increased and viability of LAB decreased. Increased storage time made bioactive compounds and viability of LAB decreased. The amount of bioactive compounds on black mulberry yoghurt after 20 days storage ranged from 49,20-99,14 µg GAE/g yoghurt, 101,91- 146,27 µg CE/g yoghurt, and 7,96-23,89 µg cya-3-glu/g yoghurt with ALT value ranged from 9,4804-9,5997 log cfu/mL and pH 3,877-3,961.